2020
DOI: 10.1002/adem.202000207
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Structures of Graphene and Pt Nanoparticles: A Multiscale Computational Study

Abstract: Multiscale simulation study results of multilayer structures consisting of graphene sheets with embedded Pt nanoparticles is reported. Density functional theory is used to understand the energetics of Pt–graphene interfaces and provide reference data for the parameterization of a Pt–graphene interaction potential. Molecular dynamics simulations then provide the conformation and energetics of graphene sheets with embedded Pt nanoparticles of varying density, form, and size. These results are interpreted using a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…We should note that although the pull-out force and pull-out energy increases by Pt-coating, the interface characteristics between Pt and CNT is of physically adsorbed type in which no chemical bondings between metal and CNTs are formed [61][62][63]. The only commitment between metal and CNT in this model is the weak physical interactions, which will disappear under the shear stress of less than 50 MPa [49]. Therefore, CNTs, independent on their length, start to slide inside the matrix and get pulled out as soon as the matrix ruptures, and they have little significant load-transfer strengthening effects on the Mg matrix.…”
Section: Atomistic Simulation Procedures and Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…We should note that although the pull-out force and pull-out energy increases by Pt-coating, the interface characteristics between Pt and CNT is of physically adsorbed type in which no chemical bondings between metal and CNTs are formed [61][62][63]. The only commitment between metal and CNT in this model is the weak physical interactions, which will disappear under the shear stress of less than 50 MPa [49]. Therefore, CNTs, independent on their length, start to slide inside the matrix and get pulled out as soon as the matrix ruptures, and they have little significant load-transfer strengthening effects on the Mg matrix.…”
Section: Atomistic Simulation Procedures and Resultsmentioning
confidence: 94%
“…A Morse potential of the form E M = D M [e −2α(r−r 0 ) − 2e −α(r−r 0 ) ] was used for describing Pt-C interactions, where r is the bond distance, r 0 the equilibrium bond distance, D M is the well depth, and α controls the stiffness of the potential. The parameters for Pt-C morse potentials are D M = 0.0071 eV, r 0 = 4.18 Å, and α= 1.05 Å −1 [49].…”
Section: Atomistic Simulation Procedures and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…([53, 58, 59]). The only commitment between metal and CNT in this model is the weak physical interactions, which will disappear under the shear stress of less than 50 MPa ( [47]). Therefore, CNTs, independent on their length, start to slide inside the matrix and get pulled out as soon as the matrix ruptures, and have little significant load-transfer strengthening effect on the Mg matrix.…”
Section: Atomistic Simulation Procedures and Resultsmentioning
confidence: 99%
“…Si et al [46] showed that the decoration of exfoliated graphene sheets with Pt nanoclusters prevents face-to-face graphene aggregation. Atomistic simulation study of multilayer structure of graphene and Pt nanoparticle found an optimum nanoparticle density where the adhesive energy of the structure is lowest, and thus the separation of the graphene sheets most easy [47].…”
Section: Introductionmentioning
confidence: 99%